Empirical characterization of test platform effects on single-axis CubeSat reaction wheel ADCS with IoT-based PID tuning - Bayu Nuar Khadapi Hasibuan; Dananjaya Ariateja; Satriya Utama; Rangga Taqwa; Ria Aprilianingsih (International Journal of Enterprise Modelling, 2026)
Terrestrial testing of CubeSat Attitude Determination and Control System (ADCS) prototypes presents fundamental validation challenges because no laboratory platform perfectly replicates the free-floating microgravity condition of orbit. The empirical effect of such platform-induced dynamics on closed-loop reaction-wheel control performance, particularly for low-cost academic CubeSat programs, remains insufficiently characterized. This study aims to empirically compare two widely used low-cost test platforms a string suspension and a free bearing for a single-axis reaction-wheel ADCS prototype and to quantify how each platform’s parasitic dynamics constrain PID controller performance. A 1.5U CubeSat-class prototype with an ESP32-based controller, BNO055 IMU, and a Blynk Cloud IoT interface for real-time PID tuning was tested over five sessions (>1 hour of cumulative active testing). Performance was quantified using the Time-in-±5° metric, error standard deviation, settling time, and number of direction reversals. Quantitative results show that the string suspension yields a peak Time-in-±5° of 8.8% with error standard deviation of ±90.7–119.9°, driven by torsional-pendulum dynamics, while the free bearing yields a peak Time-in-±5° of only 1.2% with a stuck-and-jump signature characteristic of stiction. A Karnopp-friction simulation in Python reproduces a permanent steady-state error of ~5° under stiction, quantitatively validating stiction as the dominant non-linearity. The novelty of this work lies in the integrated combination of empirical multi-platform characterization, Karnopp-based stiction validation, and an open-source IoT-based PID tuning framework within a single low-cost experimental system, providing actionable guidance for academic CubeSat ADCS development under limited-facility conditions.